THE FEATURES OF TIBIOFIBULAR INJURY IN PATENTS WITH ANKLE FRACTURES - N. F. Fomin; A. G. Ovdenko; R. A. Nadjafov; A. N. Bogdanov (Travmatologiâ i Ortopediâ Rossii, 2016)
The role of interposition of soft tissues into tibiofibular syndesmosis is analyzed as a cause of unsatisfactory outcomes in the ankle joint pronation fracture treatment. The study is based on clinical (452 patients) and experimental material (36 experiments) including unfixed anatomic objects. The elevator for minimal invasive operative elimination of interposition of stumps of distal tibiofibular syndesmosis anterior and posterior ligaments is developed and tested.